Biomorphological scaling laws from convectively accelerated streams. Issue 3 (20th January 2020) - Calvani, Giulio; Perona, Paolo; Schick, Coralie; Solari, Luca
Abstract: Worldwide convectively accelerated streams flowing in downstream‐narrowing river sections show that riverbed vegetation growing on alluvial sediment bars gradually disappears, forming a front beyond which vegetation is absent. We revise a recently proposed analytical model able to predict the expected longitudinal position of the vegetation front. The model was developed considering the steady state approximation of 1‐D ecomorphodynamics equations. While the model was tested against flume experiments, its extension and application to the field is not trivial as it requires the definition of proper scaling laws governing the observed phenomenon. In this work, we present a procedure to calculate vegetation parameters and flow magnitude governing the equilibrium at the reach scale between hydromorphological and biological components in rivers with converging boundaries. We collected from worldwide rivers data of section topography, hydrogeomorphological and riparian vegetation characteristics to perform a statistical analysis aimed to validate the proposed procedure. Results are presented in the form of scaling laws correlating biological parameters of growth and decay from different vegetation species to flood return period and duration, respectively. Such relationships demonstrate the existence of underlying selective processes determining the riparian vegetation both in terms of species and cover. We interpret the selection of vegetation species from ecomorphodynamic processes occurring in convectively accelerated streams as the orchestrated dynamic action of flow, sediment and vegetation characteristics. © 2019 John Wiley & Sons, Ltd. Abstract : We revise a river eco‐morphodynamic model to account for time scales. We correlate vegetation properties to hydrological timescales. We demonstrate rivers to be able to select vegetation species according to bio‐morphological properties.